Experimental assessment on the solar energy storage by using chemical-looping combustion - Jiang, Q. (2020)
This paper put forward a new method that using the perovskite–type oxide (LaCuxNi1-xO3) as the solar thermal energy storage material which can drop the reduction temperature to below 500℃ that parabolic-trough solar collectors could reach. Herein, LaCuxNi1-xO3(x =0, 0.1, 0.2, 0.3, 0.5) is synthesized and investigated. Besides, the physical and chemical properties of LaCuxNi1-xO3 are tested by XRD, SEM and BET, and the reactivity and generation are studied through experiments by means of thermogravimetric analyzer (TGA). Experimental results indicate that these five oxygen carriers are of high porosity and this porous structure benefits from doping by Cu at B-site when LaCuxNi1-xO3 reacts with methane at 350℃, it exhibits great performance such as high reproducibility and good resistance for carbon formation. No obvious sintering is appeared after 30 times multiple redox cycles and LaCu0.1Ni0.9O3 is able to be reoxidized to initial oxidation state.